Corrosion resistance of stainless steels - Dillon, C.P (Corrosion technology (New York, N.Y.), 1995)
Examines the corrosion of stainless steels and similar chromium-bearing nickel-containing higher alloys, detailing various corrosive environments, including atmospheric and fire-side corrosion, corrosion by water and soil, and corrosion caused by particular industrial processes.